The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1073/pnas.71.7.2791
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Synthesis of Malformin A

Abstract: A structure (the disulfide form of cyclo-D-cysteinyl-L-valyl-D-cysteinyl-D-leucyl-L-isoleucyl), previously proposed for malformin A, was reexamined. On the basis of chemical degradations, a different structure (the disulfide form of cyclo-D-cysteinyl-D-cysteinyl-L-valyl-Dleucyl-L-isoleucyl) was established. Accordingly, a compound with this structure was synthesized and was found to be identical with malformin A. The synthetic product causes curvatures on corn roots; maximum effect was seen at a concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The present work has demonstrated that the enzyme which catalyzes the a$-elimination reaction of D-cysteine, D-cysteine desulfhydrase, occurs in E. [32], contain Dcysteine as a component. Therefore, it might be possible that D-cysteine desulfhydrase takes part in the detoxification of catabolic degradation of D-cysteine-containing toxic compounds, which happen to invade or to be produced in bacterial cells.…”
Section: Serological Propertiesmentioning
confidence: 60%
“…The present work has demonstrated that the enzyme which catalyzes the a$-elimination reaction of D-cysteine, D-cysteine desulfhydrase, occurs in E. [32], contain Dcysteine as a component. Therefore, it might be possible that D-cysteine desulfhydrase takes part in the detoxification of catabolic degradation of D-cysteine-containing toxic compounds, which happen to invade or to be produced in bacterial cells.…”
Section: Serological Propertiesmentioning
confidence: 60%
“…Malformin, cyclo-D-cysteinyl-D-cysteinyl-L-valyl-L-leucyl-Lisoleucyl (2), is a potent plant growth regulatory produced by the fungus Aspergillus niger (4). The ability of malformin to stimulate plant growth in light was recently shown to involve phytochrome (8).…”
mentioning
confidence: 99%
“…The less hindered amide bond between D-cysteine and L-valine was chosen for cyclization because the cyclization position between Dleucine and L-isoleucine has already been investigated in the stepwise synthesis of malformin A1 [7].…”
Section: Resultsmentioning
confidence: 99%